Water efficiency infrastructure and energy requirements at the research house - Kele, B.; Hoffman, K.; Wolfs, Peter; Tomlinson, I.; Midmore, D. (Lanfax Laboratories, 2005)
Research House is part of the Queensland Department of Housing's 'Towards Healthy and Sustainable Housing Research Project'. The aim of the venture was to construct a house with sustainable building design and test how the features worked with a rental clientele. Research House was built in Rockhampton, with the data collection undertaken by the Central Queensland University (CQU). The house is equipped with a 75-channel data logger that continuously collected water use, energy use and generation, temperature, and rainfall information. As the house was designed for the rental market, the sustainable features of the house are passive in nature requiring no or very little direct manipUlation by the householder. Water efficient infrastructure, such as flow-reduced taps and a front-loading washing machine, were installed throughout the house. All wastewater-generating infrastructure and garden irrigation implements were equipped with a water meter and individually monitored. The electrical demands of the house and the electricity generation through solar panels were also observed. The waterusefigures and total energy requirements of Research House have been collected and collated for more than two years. These data allow for a partial evaluation of the sustainable design of Research House.